Oncolytic vaccinia virus expressing a bispecific T-cell engager enhances immune responses in EpCAM positive solid tumors - Wei, Min; Zuo, Shuguang; Chen, Zhimin; Qian, Peng; Zhang, Yenan; Kong, Lingkai; Gao, Honglan; Wei, Jiwu; Dong, Jie (Frontiers in Immunology, 2022)
Insufficient intratumoral T-cell infiltration and lack of tumor-specific immune surveillance in tumor microenvironment (TME) hinder the progression of cancer immunotherapy. In this study, we explored a recombinant vaccinia virus encoding an EpCAM BiTE (VV-EpCAM BiTE) to modulate the immune suppressive microenvironment to enhance antitumor immunity in several solid tumors. VV-EpCAM BiTE effectively infected, replicated and lysed malignant cells. The EpCAM BiTE secreted from infected malignants effectively mediated the binding of EpCAM-positive tumor cells and CD3ε on T cells, which led to activation of naive T-cell and the release of cytokines, such as IFN-γ and IL-2. Intratumoral administration of VV-EpCAM BiTE significantly enhanced antitumor activity in malignancies with high other than with low EpCAM expression level. In addition, immune cell infiltration was significantly increased in TME upon VV-EpCAM BiTE treatment, CD8+ T cell exhaustion was reduced and T-cell-mediated immune activation was markedly enhanced. Taken together, VV-EpCAM BiTE sophistically combines the antitumor advantages of bispecific antibodies and oncolytic viruses, which provides preclinical evidence for the therapeutic potential of VV-EpCAM BiTE.